Chemical sintering of direct-written silver nanowire flexible electrodes under room temperature. (23rd June 2017) - Hui, Zhuang; Liu, Yangai; Guo, Wei; Li, Lihang; Mu, Nan; Jin, Chao; Zhu, Ying; Peng, Peng
Abstract: Transparent and flexible electrodes on cost effective plastic substrates for wearable electronics have attract great attention recently. Due to the conductivity and flexibility in network form, metal nanowire is regarded as one of the most promising candidates for flexible electrode fabrication. Prior to application, low temperature joining of nanowire processes are required to reduce the resistance of electrodes and simultaneously maintain the dimensionality and uniformity of those nanowires. In the present work, we presented an innovative, robust and cost effective method to minimize the heat effect to plastic substrate and silver nanowires which allows silver nanowire electrodes been directly written on polycarbonate substrate and sintered by different electrolyte solutions at room temperature or near. It has been rigorously demonstrated that the resistance of silver nanowire electrodes has been reduced by 90% after chemical sintering at room temperature due to the joining of silver nanowires at junction areas. After ∼1000 bending cycles, the measured resistance of silver nanowire electrode was stable during both up-bending and down-bending states. The changes of silver nanowires after sintering were characterized using x-ray photoelectron spectroscopy and transmission electron microscopy and a sintering mechanism was proposed and validated. This direct-written silver nanowire electrode with good performance has broad applications in flexible electronics fabrication and packaging.